„Die Ohnmacht ist ein Syndrom von dem Österreich.“ Heimat- und Sozialmisere in den Stücken von Thomas Arzt - Höfler, Günther A. (Studia Germanica Posnaniensia, 2020)
With reference to two plays by Thomas Arzt (Die Neigung des Peter Rosegger, Totes Gebirge), this paper examines how attitudes in contemporary Austria are represented in literature. The analysis focuses on the playwright’s poetical originality in presenting conventional themes like homeland, social misery and the Austrian sense of apocalypse. It will be argued that the transformative playing with dramatic genres, intertextuality, significant idioms and local song material is in fact a farce exposing current circumstances and mentalities.